Formal total synthesis of anti-helicobacter pylori agent (+)-spirolaxine methyl ether - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A convergent, formal enantioselective synthesis of anti-Helicobacter pylori agent, (+)-spirolaxine methyl ether 2 has been achieved in high enantiomeric purity starting from commercially available 1,5-pentanediol. The strategy mainly comprises of the Noyori's asymmetric reduction and Brown allylation/Cu-catalyzed lactonization as the key step for the construction of key chiral intermediates, spiroketal 3 and phthalide fragment 4. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Brown allylation; Cu-catalyzed lactonization; Noyori's asymmetric reduction; Phthalide; Spiroketal